2021
DOI: 10.1016/j.frl.2021.101977
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Fear of pandemic and short-term IPO performance

Abstract: This study analyzes the relationship between COVID-19 related fear and short-term IPO performance. Though the average market-adjusted initial return of IPOs in the year 2020 is higher than that of the last four decades, it decreases if fear of pandemic increases. The evidence is robust when we use matching firm-adjusted initial returns. Next, we analyze the persistence of performance after the IPO date. The results show that the performance of IPO firms is more sensitive to the fear of the pandemic than the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 56 publications
4
60
1
2
Order By: Relevance
“…Not only that, but underpricing stocks also decreased steadily and consistently every week, accompanied by a decrease in the correlation coefficient. This is, however, consistent with the literature, which shows the initial return during pandemic tend higher in the initial day but decreases after several weeks (Mazmuder & Saha, 2021). It can be concluded that IPO shares only experience underpricing on the first day, but it is no longer statistically significant in the short term.…”
Section: Figure 1 Number Of Underpricing Stock During the Research Periodsupporting
confidence: 92%
See 1 more Smart Citation
“…Not only that, but underpricing stocks also decreased steadily and consistently every week, accompanied by a decrease in the correlation coefficient. This is, however, consistent with the literature, which shows the initial return during pandemic tend higher in the initial day but decreases after several weeks (Mazmuder & Saha, 2021). It can be concluded that IPO shares only experience underpricing on the first day, but it is no longer statistically significant in the short term.…”
Section: Figure 1 Number Of Underpricing Stock During the Research Periodsupporting
confidence: 92%
“…The latest research of COVID-19 pandemic study-related underpricing was Mazmuder & Saha (2021). They investigated the impact of fear associated with the pandemic on IPO stock at NYSE, NASDAQ, and AMEX, and are ADRs.…”
mentioning
confidence: 99%
“…The retail investors paid more attention to the FEARS terms. Mazumder and Saha (2021) This study proxies the fear by constructing the equally weighted index of both newly infected cases and deaths over the period from January-2019 to July-2020. The set of IPO firms’ characteristics were employed for regression to see how the IPO firms perform during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, global stock market volatility increased sharply while the stock prices dropped aggressively amid an unprecedented disruption to the global economic prospects and world trade. As a result, a growing stream of literature has emerged, aiming at analyzing the adverse impact of uncertainty and fear related to the COVID-19 pandemic in different contexts, for example, stock market performances ( Baig et al., 2021 ; Cepoi, 2020 ; Topcu and Gulal, 2020 ; Ashraf, 2021 ; Corbet et al., 2021 ), commodity and cryptocurrencies markets ( Bakas and Triantafyllou, 2020 ; Conlon and McGee, 2020 ; Salisu et al., 2020 ; Amar et al., 2021 ;), and primary equity markets ( Baig and Chen, 2021 ; Mazumder and Saha, 2021 ).…”
Section: Introductionmentioning
confidence: 99%